Perceived Coach Leadership Profiles and Relationship With Burnout, Coping, and Emotions - González-García, Higinio; Martinent, Guillaume; Trinidad Morales, Alfonso (Frontiers in Psychology, 2019)
The aims of the study were to identify coach profiles and examine whether participants from distinct profiles significantly differed on burnout, emotions and coping. A sample of 268 athletes (Mage = 29.34; SD = 12.37), completed a series of self-reported questionnaires. Cluster analyses revealed two coach leadership profiles: (a) profile 1 with high scores of training and instruction, authoritarian behavior, social support and positive feedback, and a low score of democratic behavior; and (b) profile 2 with low levels in training and instruction, authoritarian behavior, social support and positive feedback and high levels in democratic behavior. Results of MANOVAs indicated significant differences across coach profiles on reduced accomplishment, sport devaluation, happiness and seeking support and marginal differences on dejection, logical analysis, imagery/thought control, and excitement. Moreover, coach leadership profiles were not confounded by demographic variables (level of competition, gender, age, number of practice hours, professional versus no professional athletes). As a conclusion, the profile approach offered a holistic way to examine coach leadership in sport as two distinct coach profiles emerged from the cluster analyses with an unexpected combination of coach leadership dimensions.